TIKTOK SEBAGAI SOCIAL MEDIA COMMERCE: DINAMIKA MEDIA DAN UMKM PASCA KEPUTUSAN PERMENDAG RI NO. 31/2023 - Herman Purba; Edo Rinaldo; Dian Kartika Fitri; Kiki Utami (KAGANGA KOMUNIKA: Journal of Communication Science, 2026)
The presence of TikTok Shop as a feature that allows users to engage in buying and selling transactions is considered the main cause of bankruptcy affecting several Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, which ultimately prompted the issuance of the Ministry of Trade Regulation (Permendag) No. 31 of 2023. This issue has since become a topic of public discussion, widely covered in the mass media from various perspectives. This study aims to apply Robert N. Entman’s framing analysis, focusing on how two online mass media outlets, Detik.com and Kompas.com, reported on the closure of TikTok Shop. The research adopts a qualitative approach supported by Entman’s framing analysis, which consists of four analytical elements: defining problems, diagnosing causes, making moral judgments, and making treatment recommendations. The findings indicate that Detik.com and Kompas.com tend to employ different framing approaches in their reporting on the TikTok Shop closure. Detik.com presents a more critical framing of the government’s policy, while Kompas.com adopts a more empathetic framing toward the MSMEs affected by the closure. Detik.com’s reports primarily focus on the government policy aspect, whereas Kompas.com emphasizes the ongoing trade transactions and the impacts on MSMEs that have relied on TikTok Shop’s services. This difference in framing influences how readers perceive the government’s policy regarding the closure and shapes public understanding of its impact on business actors and consumers alike.   Keywords: Framing Analysis, Mass Media, Detik.com, Kompas.com, TikTok Shop.